Faktor-Faktor Yang Mempengaruhi EVA - Thomas Sumarsan Goh; Erika Erika; Rahel Yunita (Owner : Riset dan Jurnal Akuntansi, 2023)
Capital structure, return on invested capital (ROIC), fixed assets, and net operating profit after tax (NOPAT) are the factors that affect economic value added (EVA). Understanding the potential effects of the independent factors on the dependent variable, which is economic value added (EVA), is the goal. Descriptive statistics, the traditional hypothesis tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), the t-test and F-test, and coefficient of determination were all used in this work. According to descriptive statistics, the data is normal and passes the traditional assumption test. Capital structure largely has no effect on EVA. Significant effects of ROIC, Fixed Assets, and NOPAT on EVA. EVA is impacted simultaneously by the capital structure, ROIC, fixed assets, and NOPAT. The capital structure, ROIC, fixed assets, and NOPAT are independent variables that have an impact on 35.2% of the dependent variables, while other variables have an impact on 64.8%.